Financial Development and Economic Growth in Iran, Based on a Nonlinear Regression - Zahra Azizi; Morteza Khorsandi (فصلنامه پژوهش‌های اقتصادی ایران, 2013)
In recent years, several studies have examined the relationship between financial development and economic growth. But even considering the same Indicators of financial development, findings of these studies have been different. The existence of non-linear relationships can be one of the reasons for these differences. In this paper using the smooth transition regression method, we examine a nonlinear relationship between financial development and economic growth in Iran. The tests of linearity, transition variable election and transition function determination results confirms the existence of non-linear relationship between financial development and economic growth by considering time trend as a transition variable.  The appropriate transition function is LSTR1 that is a logistic function form with one threshold. As a result a regime change in the relationship between financial development and economic growth occurred in about 1989, ( i.e. at the end of the war ). This regime switching can also be considered as a cause for difference in findings of similar studies in Iran.